2018
DOI: 10.1177/000313481808401243
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Evaluations of the Effects of Noise on Mental Workloads Based on Pupil Dilation during Laparoscopic Surgery

Abstract: Noise can exert undeniable pressure on human minds, especially during tasks that require high precision and attention, such as those performed during surgery. To investigate whether auditory stimuli increases mental loads during laparoscopic surgery, we examined the effects of operating room (OR) noises and music by measuring mean changes in pupil sizes and subjectively assessing performances during surgery. We recruited 24 subjects with varying laparoscopic surgery experience levels to perform complete append… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(45 citation statements)
references
References 44 publications
(38 reference statements)
0
45
0
Order By: Relevance
“…However, as the noise level increases, workload levels of the OR staff also increase. Parallel to this finding, intraoperative noise increased workload levels among the anesthesia team in the study by McNeer et al 12 Gao et al 13 also reported that intraoperative noise increases the surgeon's mental workload (referring to the mental effort required by the task, eg, thinking, deciding, calculating, and remembering).…”
Section: And 723 Db(a)mentioning
confidence: 82%
“…However, as the noise level increases, workload levels of the OR staff also increase. Parallel to this finding, intraoperative noise increased workload levels among the anesthesia team in the study by McNeer et al 12 Gao et al 13 also reported that intraoperative noise increases the surgeon's mental workload (referring to the mental effort required by the task, eg, thinking, deciding, calculating, and remembering).…”
Section: And 723 Db(a)mentioning
confidence: 82%
“…These resources are then no longer available for the task being performed and performance is impaired [21,22]. This view is supported by studies which have measured workload and shown that it is increased in noise [23,24,25,26,27]. In addition, the extra workload may lead to increased stress and, in the long term, chronic health problems.…”
Section: Effects Of Noise On Performancementioning
confidence: 97%
“…These resources are then no longer available for the task being performed and performance is impaired [21,22]. Results from a number of studies [23,24,25,26,27] show that noise increases mental workload. Information overload has been studied extensively, and the aim of the present research was to examine the effects of information overload on the wellbeing and academic attainment of university students.…”
Section: Effects Of Noisementioning
confidence: 99%